The contact between sports talent identification and tracking of tall and short height - Tanaka, H.; Fujii, K.; Ogura Y. (American Journal of Sports Science, 2021)
Understanding the qualities of elite athletes is necessary in trying to determine ability as sports talent. However, there are few findings based on analyses that objectively grasp the characteristics of exceptional athletes. If the characteristics of changes with age in tall and short height ranking could be clarified, the physical characteristics of tall and short height judged to be advantageous in certain sports could be identified. In this study, we analyzed the tracking status of tall and short individuals and verified the changes in height ranking level with changes in age. We then verified a logical system for the viewpoint of sports talent identification from the genetic contribution to height after birth. We then established a span evaluation chart for height with age using the wavelet interpolation model, and demonstrated the tracking of height rankings. In other words, individuals ranked as short or tall moved within that rank without change into adulthood. The major significance of this study is thought to be that, by verifying the tracking phenomenon for height, it paradoxically revealed a potential methodology for discussing heritability. By elucidating the tracking of height ranking, a logical system for the viewpoint of identifying sports talent based on the genetic contribution to height after birth could be seen in this study. Thus, if people with superior athletic ability and tall height could be identified from a very young age, it would lead to the identification of future talent in sports where height is an advantage. In sports where short height is an advantage, identifying individuals with superior athletic ability and short height would be beneficial. Therefore, a logical system for sports talent identification may have been established in this study by establishing a tracking analysis for tall and short height rank.